Dynamic Tensile Properties of Clay Bricks. (February 2022) - Zhang, Xihong; Chiu, Yu-Wen; Hao, Hong
Abstract: It is commonly known that materials behave differently under static and dynamic loads. There is still a lack of understanding of dynamic material properties of clay bricks. Our previous study investigated the dynamic compressive properties of clay bricks. This paper focuses on the dynamic tensile properties of clay bricks. Quasi-static and dynamic tests are carried out on three types of clay bricks, i.e., high-strength Copper Brown, mid-strength Limestone Hue, and low-strength Common Solid bricks. Both direct tensile test and indirect split-tensile test (Brazilian disc test) are conducted to determine the brick tensile properties at various strain rates. Dynamic tensile strength, corresponding failure strain, Young's modulus at strain rates between 1.33 × 10 −6 s −1 and 26 s −1 are determined. Correlation between dynamic split-tensile strength and dynamic direct tensile strength is examined and a conversion relationship is proposed. The results are compared with existing data on brick, mortar and concrete. An empirical formula of DIF (dynamic increase factor) for brick tensile strengths at different strain rates are derived for easy and accurate engineering analysis and numerical modelling of clay brick response under dynamic loading. Highlights: Quasi-static and dynamic tensile properties of clay bricks are investigated. Material properties at strain rate covering 1.33 × 10 −6 s −1 and 26 s −1 are determined. Both direct tension test and split-tension test are conducted. The direct tensile and split-tensile strengths are correlated. Empirical design formula are derived.